2006
DOI: 10.2217/14750708.3.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of drug-eluting stents in patients with diabetes

Abstract: Numerous genes whose expression is controlled by complex regulatory networks are involved in the development and progression of each cancer,and those genes will be the key factors for determining each characteristic of the tumor. The recent development of DNA microarray and related technologies provides an opportunity to perform more detailed characterization( profiling) of individual tumor cells. Indeed, the gene expression profile of a tumor provides a unique molecular portrait or signature that can be corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In addition, in vitro and in vivo studies have demonstrated a clear modulation of immune functions by several whey protein-derived products [14]. Furthermore, whey peptides possess immunomodulatory activities, such as stimulating lymphocytes and increasing phagocytosis, and the secretion of immunoglobulin A (IgA) from Peyer's patches [15]. Recently, it has been reported that WP has immunomodulatory properties and the potential to increase host defense [16], protective effects against childhood asthma and atopic syndrome [17], and anticancer effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in vitro and in vivo studies have demonstrated a clear modulation of immune functions by several whey protein-derived products [14]. Furthermore, whey peptides possess immunomodulatory activities, such as stimulating lymphocytes and increasing phagocytosis, and the secretion of immunoglobulin A (IgA) from Peyer's patches [15]. Recently, it has been reported that WP has immunomodulatory properties and the potential to increase host defense [16], protective effects against childhood asthma and atopic syndrome [17], and anticancer effects [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of esophageal squamous cell carcinoma (ESCC) and CDDP, the overexpression of multidrug-resistant protein gene (MRP1/2) ( 9 , 10 ) and the zinc ribbon domain-containing-1 (ZNRD1) ( 7 ) have been reported to be involved in this resistance. A number of methods have been used to identify genes involved in resistance to chemotherapy, including microarray, expression profiling, cDNA library screens, RNAi library screens and small molecule inhibitor screens ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%